OPTIMALISASI PENGGUNAAN TEKNOLOGI DIGITAL DALAM MENGATASI SAMPAH ELEKTRONIK (E-WAste) DI INDONESIA PADA ERA DISRUPTIF - Syafuro Lailatun Naza; Anjani Nur Safna; Ichsan Fauzi Rachman (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to find effective solutions to the problem of electronic waste (e-waste) in Indonesia in a disruptive era, an era where digital technology is experiencing rapid development and influencing human life patterns. The use of electronic devices in this era has also increased significantly due to the consumerist behavior of people who tend to buy new electronic goods and throw away old ones even though they are still in a usable condition. This creates piles of electronic waste which pose a risk to the environment and health, because electronic waste contains dangerous components. The research method used is a literature review method which involves collecting and analyzing various reference sources such as scientific journals, books, reports and articles. The research results show that the role of the government and society is very important in overcoming the problem of electronic waste in Indonesia, for example using technology wisely so as to maximize the use of electronic goods, selling or even donating old electronic equipment, renting electronic goods if needed for temporary use, and making informed decisions. be wise in purchasing new electronic goods, and recycle electronic waste.